Large-Eddy Simulation of Arctic Stratocumulus: Process Representation and Surface Heterogeneity - Rauterkus, Robert (2021)
Small-scale processes are crucial for the evolution of Stratocumulus and act on scales reaching down to less than one meter. Most large-eddy simulation studies still apply a horizontal resolution of tens of meters, limiting the ability to resolve cloud-driving processes. I investigate such small-scale processes in a reference case that is—based on the recent field campaigns ACLOUD and PASCAL—defined within this thesis to represent a mixed-phase Stratocumulus during Arctic spring. I apply large-eddy simulations with horizontal resolutions of 35m, 10m, 3.5m, and 3m and a vertical resolution of about 3m. My analysis focuses on the resolution sensitivity of cloud-top entrainment processes and the effects of surface heterogeneity structure on the atmospheric boundary layer. First, I find that for a horizontal grid spacing larger than 10m, the effects of small-scale microphysical cooling and turbulent engulfment on cloud-top entrainment are only represented sufficiently for the atmospheric boundary layer bulk profiles but not on a process level. The stratification-limited size of energy-containing eddies violates the assumptions underlying many sub-grid scale models of turbulent mixing. Second, I observe a decrease in cloud-top entrainment for a horizontal resolution coarser than 10m, which results in 15% more cloud water after six hours of simulation and a corresponding optical thickening of the Stratocumulus. Third, I find that structuring surface heterogeneity does not affect zero- and first-order bulk quantities outside the surface layer. A notable sensibility in higher altitudes is only observed for higher-order quantities, which show increased values over structured surface heterogeneity. Fourth, I observe structured surface heterogeneity to form a streamwise elongated, roll-like, secondary circulation perpendicular to the mean wind. Its formation is neither captured by traditional Arctic lead theory nor by the theory of surface heterogeneity effects on cloud-free atmospheric boundary layers. It turns out that ...